1988
DOI: 10.1083/jcb.107.1.353
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the major proteins that promote neuronal process outgrowth on Schwann cells in vitro.

Abstract: Abstract. Schwann cells have a unique role in regulating the growth of axons during regeneration and presumably during development. Here we show that Schwann cells are the best substrate yet identified for promoting process growth in vitro by peripheral motor neurons. To determine the molecular interactions responsible for Schwann cell regulation of axon growth, we have examined the effects of specific antibodies on process growth in vitro, and have identified three glycoproteins that play major roles. These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
235
0
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(242 citation statements)
references
References 76 publications
3
235
0
1
Order By: Relevance
“…Antibodies against N-cadherin inhibit neurite outgrowth in vitro on astrocytes and Schwann cells (Tomaselli et al, 1988;Bixby et al, 1988). In general, antibodies against cadherins disrupt cell-cell contacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies against N-cadherin inhibit neurite outgrowth in vitro on astrocytes and Schwann cells (Tomaselli et al, 1988;Bixby et al, 1988). In general, antibodies against cadherins disrupt cell-cell contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of N-cadherin mRNA into early frog embryos results in abnormal nervous system formation (Detrick et al, 1990). Antibodies against N-cadherin inhibit neurite outgrowth in vitro on astrocytes and Schwann cells (Tomaselli et al, 1988;Bixby et al, 1988) and disrupt 0 1992 WILEY-LISS, INC somite explants into single cell sheets .…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors are prerequisites for the survival and axonal regeneration of damaged neurons. [7][8][9] Neurotropin-3 (NT-3) is one of the important neurotrophic factors. It can prevent atrophy of mature CNS neurons, and promote corticospinal tract axonal regeneration and recovery of hindlimb's function in spinal cord injured animal [10][11][12][13][14][15] and Hapner et al 16 had indicated that NT-3 could upregulate the TrkC expression of NSCs and promote for them to differentiate into neurons.…”
Section: Introductionmentioning
confidence: 99%
“…First, antibodies recognizing N-cadherin inhibit neurite growth on the surfaces of several types of nonneuronal cells (e.g., Bixby et al, 1987Bixby et al, , 1988Tomaselli et al, 1988). Second, immortal cells transfected with a cDNA clone of the gene encoding N-cadherin are a much better substrate for neurite growth from retinal explants than the control, untransfected cells (Matsunaga et al, 1988a).…”
mentioning
confidence: 99%
“…More recently, examination of process outgrowth induced by the surfaces of other cells has strongly suggested a role for cell adhesion molecules in this process (Bixby et al, 198% 1988;Chang et al, 1987;Tomaselli et al, 1988;Seilheimer and Schachner, 1988). The particular cell adhesion molecules that are involved include L1 Lagenauer and Lemmon, 1987;Bixby et al, 1988); the Ll-related molecules, FI1 (contactin) and neurofascin Rathjen et al, 1987;Brummendorf et al, 1989;Ranscht, 1988); neural cell adhesion molecule (N-CAM) (Bixby et al, 1987;Neugebauer et al, 1988;Doherty et al, 1989); and N-cadherin (references cited above). Some evidence suggests that the myelin-associated glycoprotein may also be involved in neurite extension (Johnson et al, 1989).…”
mentioning
confidence: 99%